COMPARITIVE EVALUATION OF JATROPHA CURCAS LEAVES EXTRACT FOR ANTIBACTERIAL, ANTI-AVIAN INFLUENZA A VIRUS (H5N1) PROPERTIES AND GC-MS PROFILE - F.K. EL-BAZ,; O. BAGATO,; H.F. ALY,; S A. SAAD,; M.A. ALI,; A.A. MOHAMED, (International Journal of Pharma and Bio Sciences, 2015)
The potent antibacterial and antiviral activity of petroleum ether, ethyl acetate, successive and crude methanolic extracts of J. curcas leaves was evaluated. The antibacterial activity of J. curcas extracts was studied against 6 common foods borne bacteria using disc diffusion assay. The antibacterial activity of J. curcas extracts showed different degrees of inhibition zone against the pathogens bacteria. Yet, successive methanolic and ethyl acetate extracts were effective against most of the tested strains. Additionally, all J. curcas extracts were evaluated against the highly pathogenic H5N1 influenza virus (A/chicken/Egypt/M7217B/2013 (H5N1)) using plaque reduction assay. Crude methanolic extract showed antiviral activity with virucidal effect of 75% at concentration 25 µg/µl. The GC-MS analysis of petroleum ether and ethyl acetate extracts revealed the presence of major active constituents. The present study may suggest the possibility for developing new antibacterial and antiviral compounds from J. curcas leaves.